Voltage Clamp Electrophysiology Screening Of Selected Compounds From Zizyphus Mauritiana And Myristica Fragrans On Specific GABA Receptors - Che Has, Ahmad Tarmizi (2012)
This study focused on the effects of the methanol crude extract of Zizyphus mauritiana leaves and the essential oil of the mesocarp of Myristica fragrans on the function of GABA (A) receptors. Both crude and essential oil were tested on the Xenopus laevis oocytes that comprised of GABA (A) receptors α1β2γ2s subtype. An automated fast perfusion system that applied the two microelectrodes voltage clamp measurement technique at EC5-10 of GABA was used. GABA or gamma-aminobutyric acid is the major inhibitory neurotransmitter in the mammalian central nervous system and involves in the balance between excitation and inhibition in the neuronal cells.